Mobile Robots and Autonomous Vehicles in the Mobility as a Service (MAAS) Concept - Yevsieiev, V. (My University, 2025)
The development of autonomous vehicles and mobile robots plays a key role in the concept of Mobility as a Service (MaaS), which aims to integrate various transport solutions into a single digital ecosystem. The use of artificial intelligence, the Internet of Things (IoT) and cyberphysical systems allows for effective urban transport management, congestion reduction and resource optimization. The article examines the technological aspects of the development of autonomous mobile systems within MaaS, their advantages and implementation challenges. The impact of autonomous transport on the sustainability of urban ecosystems, environmental aspects and prospects for integration into modern cities are analyzed.
Keywords: mobile robots; autonomous vehicles; Mobility as a Service; urban mobility; artificial intelligence; transport automation